Probing the role of associative polymer on scCO2-Foam strength and rheology enhancement in bulk and porous media for improving oil displacement efficiency - Hanamertani, A.S. (Elsevier Ltd, 2021)
Foam mobility control technique has been extensively applied to encounter unfavorable sweep efficiency during CO2 injection in heterogeneous reservoirs. Harsh reservoir conditions have encouraged a need of effective mobility control agent. In this study, we present a comprehensive experimental investigation utilizing a newly developed water-soluble associative polymer as additive to foam system for stability and rheology enhancement. The performance of polymer enhanced foam on residual oil displacement was also evaluated in porous media. A significant increment in foam longevity and improved foam rheological behavior were obtained with associative polymer presence. Compared to conventional polymer's performance, the associative polymer enhanced foam could establish the higher flow resistance and better compatibility with reservoir conditions. The addition of associative polymer profoundly increased the foam apparent viscosity and gas mobility reduction factor at optimum foam quality in the absence and presence of oil. A noticeable improvement in oil recovery efficiency was also observed in the case with associative polymer by which 28 incremental oil recovery was achieved, 14 higher than that obtained from polymer-free foam injection. The utilization of associative polymer enhanced foam is considered promising for a deepers foam propagation in the formation to recover substantial amount of residual oil. Â© 2021 Elsevier Ltd